Effects of subacute moderate hypoxia on performance, peak oxygen uptake and stroke kinematics in 50- to 400-m trials in eltie swimmers - Rodriguez, F. A.; Chaverri, D.; Mercade, J. J.; Argüelles, J.; Morales, E.; De La Fuente, B.; Feriche, B.; Calderon, C.; Barrero, A.; Iglesias, X. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Introduction: Exposure to moderate hypoxia negatively impacts many physiological responses to maximal exercise (e.g. decreased cardiac output and muscle recruitment, increased cost of ventilation) and impairs aerobic performance, whereas short duration, anaerobic exercise is not much affected. The effect of acute hypoxia on physiological and technical performance in swimmers has been investigated during submaximal 1 but not during maximal swimming exercise. We analysed the effects of subacute exposure to moderate altitude within a range of distances on maximal swimming performance, peak V02 and stroke kinematics in elite swimmers. Method: Nine elite swimmers (8 M, 1 F) performed an incremental 4x200 m front crawl test (T4x200) for VO2max· On separate days, they performed time trials in a 50-m indoor pool: 50 and 400 m front crawl (TT50, TT400) and 200 m at best personal stroke (TT200). They were tested both under normoxic (NORM) and hypoxic conditions (HYPO) -72 h after arrival to an altitude of 2,320 m (CAR Sierra Nevada, Spain). Respiratory gases were collected breath-by-breath for 1 to 3 min during the immediate recovery. Peak V02 was taken as the first post-exercise 20-s average. Swim trials were video recorded with 3 lateral cameras (50Hz), 2 placed underwater and 1 outside the water. Final time (t) and 3-cycle stroke rate (SR), stroke length (SL), and stroke index (SI) were assessed on each trial. Differences in peak V02 measured in the different tests were assessed using AN OVA for repeated measures. Differences between NORM and HYPO were assessed using the two-tailed paired t-test (P<0.05 for significance). Results: Under NORM conditions, there were no significant differences between VO2max (3,555 ± 827 ml/min) and VO2peak measured at TT50 (3,246 ± 732 ml/min) TT200 (3,341 ± 766), or TT400 (3,331 ±648) (P=0.25). Under HYPO conditions, there were no differences in V02peak measured at TT50 (2,955± 501 ml/min), TT200 (2,921 ± 524), or TT400 (2,856 ± 476) (P=0.59). When comparing measurements under NORM and HYPO conditions, there were not differences in TT50 in any of the parameters. In contrast, in TT200 and TT400 there was a decrease in performance (2.9 ± 1.6% and 1.2± 1.2%, respectively, mean ± SD), peak V02 (12 ± 6% and 14 ± 10%), and SI (4.1 ± 3.8% and 5.8 ± 3.0%). Conclusions: Acute exposure to moderate altitude (2,320 m) does not affect sprinting ability (-30 s), whereas it impairs middle-distance performance (-2-5 min), VO2peakl and stroking efficiency, likely as a consequence of early fatigue caused by centrally-limited 0 2 delivery to the exercising muscles.